SCREENING FOR NATURAL PRODUCTS OF SHOREA Spp. AND ANISOPTERA Spp. OF THE FAMILY DIPTEROCARPACEAE FROM PASIR MAYANG, JAMBI, SUMATERA - HILMAN AFFANDi; ARIF NURYADIN; SUSILO B. PRAYOGA (BIOTROPIA, 1999)
Screening of 12 species of  Shorea  and 2 species of  Anisoptera  from the forest of Pasir Mayang, Jambi with brine shrimp (Anemia salina) lethality bioassay showed that Shorea gibosa and Anisoptera marginata  have sufficient activity for further investigation. Bioassay-guided fractionation of the active extract of  S. gibosa  led to the isolation of stigmasterol and the shoreaphenol. Bioassay-guided fractionation of the active extract of A. marginata resulted in the isolation of lupenone and 3-methoxy-4-hydroxybenzoic acid O-p-C glucopyranoside as the bioactive compound. Key words: Plant natural products/Sftorea gibosalAnisoptera marginatalActive extracts/Bioassay/Pasir Mayang.